Cobalt‐Based 3D Metal–Organic Frameworks: Useful Candidates for Olefin Epoxidation at Ambient Temperature by H2O2. Issue 29 (22nd August 2013) - Sen, Rupam; Saha, Debraj; Mal, Dasarath; Brandão, Paula; Lin, Zhi
Abstract: Two new 3D metal–organic frameworks (MOF), [Co(H2 ‐DHBDA)(bpe)] n (1 ) and [Co(H2 ‐DHBDA)(bpee)] n (2 ) [H2 ‐DHBDA = 2, 5‐dihydroxy‐1, 4‐benzenediacetate, bpe = 1, 2‐bis(4‐pyridyl)ethylene, bpee = 1, 2‐bis(4‐pyridyl)ethane], were synthesized hydrothermally. Both compounds have a similar 3D structure. The secondary building unit is a Co2 dimer with a Co··· Co distance of 4.02 Å. The hydroxy groups remain free on the surface of the compounds, and they participate in the intramolecular hydrogen bonding. A detailed structural analysis revealed that the structure is a 7‐c uninodal net with the Schläfli symbol 3 3 .4 13 .5 4 .6 and the vertex symbol [3.3.3.4.4.4.4.4.4.4.4.4.4.4.4.*.*.*.*.*.*]. The compound is catalytically active towards epoxidation reactions in heterogeneous medium with H2 O2 as an oxidant. They catalyze the epoxidation of almost all types of olefinic substrates with good efficiency. After the reaction, the catalysts can be recovered quite easily, and they can be used for further reactions without any loss of activity for several cycles. Abstract : Two cobalt‐based metal–organic frameworks were synthesized and characterized by single‐crystal X‐ray diffraction analysis. Both compounds show an interesting 7‐c net structure and are catalytically active towards epoxidation reactions, and they can be recycled up to five times without loss of activity.